Rhabdomyolysis and Acute Poisoning; a Brief Report - Pajoumand, Abdolkarim; Fahim, Farshid; Akhlaghdoust, Meisam; Zamani, Nasim; Amirfirooz, Zeinab; Dehdehasti, Mahnaz (Archives of Academic Emergency Medicine, 2018)
Introduction: Some studies have reported creatinine phosphokinase (CPK) as a new emerging way in predicting the outcomes of poisoned patients. This study aimed to evaluate the association of serum CPK level in the first 24 hours with outcomes of poisoned patients. Methods: This retrospective cross-sectional study was performed using the medical profiles of poisoned patients aged between 13 and 70 years old who were referred to the emergency department of a big referral medical toxicology center during 6 years and whose necessary data for this study was available. Results: 318 patients with the mean age of 34.9±14.5 years were studied (77.1% male). The mean serum CPK level of patients was 4693.1 ± 10303.8 (35–89480) IU/L. There was no significant correlation between serum CPK level and cause of poisoning (r= 0.16; p=0.51), age (r = -0.021; p = 0.651), sex (r = 0.131; p = 0.281), seizure (r = -0.022; p = 0.193), level of consciences (r = -0.138; p = 0.167), and duration of hospital stay (r= 0.242, p = 0.437). The mean serum CPK level was significantly higher in ICU admitted (p<0.0001), AKI (p<0.0001), hyperkalemia (p<0.0001), hypophosphatemia (p=0.045), and hypocalcaemia (p=0.008) cases. The best cut off point of serum CPK level in predicting acute kidney injury (AKI) was estimated to be 10000 IU/L (sensitivity = 83.8% and specificity = 68.8%). Conclusion: It seems that CPK could be considered as a candidate tool for screening the intoxicated patients in need for ICU admission and at risk for AKI.